Pengaruh Produktifitas Desa Wisata, Stabilisasi Ekonomi Dan Digital Marketing Terhadap Keberlanjutan Usaha Pada Balkondes Di Borobudur - Hana, Marisa Tri; Nugraheni, Nur Aisah; Shofiyani, Dianah; Candra, Septian Dwi; Nurfadhilah, Ilfi; MuhdiYanto (Universitas Muhammadiyah Metro, 2024)
A sustainable business is a company that is able to make a profit that will provide excellencefor a company or business. This research aims to look at the influence of productivity,stabilization anddigital marketing towards business sustainability at the Balcony Village inBorobudur. This research uses quantitative methods with the population in the study beingBalcondes and BUMDes managers located in 20 Balcondes in Borobudur. The sample in thisstudy was 165 respondents using a purposive sampling method. The analytical tool used ismultiple linear regression with processing using SPSS. The results of this research show thatthe productivity of tourist villages has a positive effect on business sustainability, economicstabilization has a positive effect on business sustainability anddigital marketing has apositive effect on business sustainability.